Axolotl liver regeneration is accomplished via compensatory congestion mechanisms regulated by ERK signaling after partial hepatectomy. Issue 6 (26th October 2020) - Ohashi, Ayaka; Saito, Nanami; Kashimoto, Rena; Furukawa, Saya; Yamamoto, Sakiya; Satoh, Akira
Abstract: Background: Axolotls have remarkable organ‐level regeneration capability. They can regenerate their limbs, tail, brain, gills, and heart. The liver had been considered to be a regenerative organ in these highly regeneration‐competent animals. Therefore, no research had been performed on liver regeneration in urodele amphibians. In the present study, we focused on axolotl liver regeneration and found a unique regeneration mechanism compared with other vertebrates. Results: Partial hepatectomy (PH) was performed to assess axolotl liver regeneration. Regeneration was assessed using block‐face imaging (CoMBi), histology, cell proliferation, weight gain, and Albumin ( Alb ) + area. Axolotl liver histology was compared with other vertebrates. Axolotl liver consists of Glisson's capsule, sinusoids, and hepatic cord with no apparent lobule structures. Hepatocytes were mononucleated or multinucleated. PH increased the multinucleated hepatocytes and the Alb + area, but there was no apparent liver shape recovery even 40 days after PH. Gene expression pattern suggests that no epimorphic regeneration takes place. We also found that the increase in the number of proliferating hepatocytes was regulated by ERK‐signaling. Conclusion: Our findings suggest that axolotls, which have epimorphic regeneration ability, regenerate their liver via unique mechanisms, compensatory congestion. Key Findings: Liver regeneration was not previously described in the regeneration‐competent animal, Ambystoma mexicanum. Axolotl liver has structures that are similar to those of other vertebrates. Axolotls cannot restore the liver shape after partial hepatectomy. Partial hepatectomy increased the number and multinucleation of hepatocytes, resulting in an increase in the albumin (Alb)+ area. ERK signaling regulates axolotl liver regeneration. Axolotl liver regeneration is achieved via compensatory congestion.